Pengaruh Literasi Ekonomi, Media Sosial, dan Teman Sebaya Terhadap Perilaku Konsumtif Siswa - Alhieza, Nur; Azis, Muhammad; Supatminingsih, Tuti; Najamuddin, Najamuddin (PINISI Discretion Review, 2025)
This study aims to determine the effect of economic literacy, social media, and peers on the consumptive behavior of students at SMA Negeri 11 Makassar. This research is quantitative research, research data obtained through distributing 92 questionnaires to students of SMA Negeri 11 Makassar. To test the hypothesis in this study using Partial Least Square- Structural Equation Modeling (PLS-SEM) analysis with the SmartPLS version 4.1.0.9 application program. The results of the analysis show that Economic Literacy has a positive and significant effect on consumptive behavior indicated by a p-value of 0.000 <0.05. Social media has a positive and significant effect on consumptive behavior indicated by a p-value of 0.036 <0.05. Peers have a positive and significant effect on consumptive behavior indicated by a p-value of 0.000 <0.05. Economic literacy, social media, and peers simultaneously have a positive and significant effect on consumptive behavior with a significant level of 0.000 <0.05. The R square value of consumptive behavior is 0.843, meaning that 84.3% of consumptive behavior is influenced by economic literacy, social media, and peers